α-Galactosidase A Genotype N215S Induces a Specific Cardiac Variant of Fabry Disease - Oder, Daniel; Liu, Dan; Hu, Kai; Üçeyler, Nurcan; Salinger, Tim; Müntze, Jonas; Lorenz, Kristina; Kandolf, Reinhard; Gröne, Hermann-Josef; Sommer, Claudia; Ertl, Georg; Wanner, Christoph; et al. (Circulation. Cardiovascular genetics, 2017)
Hypertrophic cardiomyopathy is the most common type of cardiomyopathy, but many patients lack sarcomeric/myofilament mutations. We studied whether cardio-specific α-galactosidase A gene variants are misinterpreted as hypertrophic cardiomyopathy because of the lack of extracardiac organ involvement. All subjects who tested positive for the N215S genotype (n=26, 13 females, mean age 49±17 [range, 14-74] years) were characterized in this prospective monocentric longitudinal cohort study to determine genotype-specific clinical characteristics of the N215S (c.644A>G [p.Asn215Ser]) α-galactosidase A gene variant. All subjects were initially referred with suspicion of genetically determined hypertrophic cardiomyopathy. Cardiac hypertrophy (interventricular septum, 12±4 [7-23] mm; left ventricular posterior wall, 11±4 [7-21] mm; left ventricular mass, 86±41 [46-195] g/m ) was progressive, systolic function mainly preserved (cardiac index 2.8±0.6 [1.9-3.9] L/min per m ), and diastolic function mildly abnormal. Cardiac magnetic resonance imaging revealed replacement fibrosis in (18/26, 69%), particularly in subjects >50 years. Elderly subjects had advanced heart failure, and 6 (23%) were suggested for implantable cardioverter-defibrillator therapy. Leukocyte α-galactosidase A enzyme activity was mildly reduced in 19 subjects and lyso-globotriaosylceramide slightly elevated (median, 4.9; interquartile range, 1.3-9.1 ng/mL). Neurological and renal impairments (serum creatinine, 0.87±0.20; median, 0.80; interquartile range, 0.70-1.01 mg/dL; glomerular filtration rate, 102±23; median, 106; interquartile range, 84-113 mL/min) were discreet. Only 2 subjects developed clinically relevant proteinuria. α-Galactosidase A genotype N215S does not lead to the development of a classical Fabry phenotype but induces a specific cardiac variant of Fabry disease mimicking nonobstructive hypertrophic cardiomyopathy. The lack of prominent noncardiac impairment leads to a significant delay in diagnosis and Fabry-specific therapy.